Cumulative effects of unemployment on health in midlife: the buffering effect of social participation - Chen, Xiaoqun; Lau, Tsz Lam; Hu, Kerui; Yuan, Jiangjun (Frontiers in Public Health, 2025)
ObjectiveThe purpose of this study was to investigate the cumulative impact of unemployment on the overall health of middle-aged and older adults in China, and to explore the moderating role of social participation and its gender differences.MethodsThis study utilized panel data from the China Health and Retirement Longitudinal Study (CHARLS). The sample included 5,973 individuals (2,830 men and 3,143 women), with respondents categorized by employment status and unemployment duration. Statistical methods included fixed effect model and factor analysis.Results(1) Unemployment significantly damages health, with more pronounced adverse effects among men than women. (2) For men, longer unemployment durations result in progressively worse health outcomes, with the greatest negative impact observed at 6–8 years of unemployment. (3) Women experience significant health declines during short-term (0–2 years) and medium-term (3–5 years) unemployment only, with no additional deterioration in long-term unemployment. (4) Informal social participation significantly buffers the negative health effects of unemployment, particularly for men, while formal social participation shows no protective effect.Conclusion(1) This study demonstrates the cumulative and gendered impact of unemployment on the health of middle-aged and older adults in China. (2) Informal social participation provides a meaningful buffer against the adverse health consequences of unemployment, particularly for men, whereas formal social activities may not offer such protection and may even have negative effects in certain scenarios. (3) These findings underscore the importance of strengthening informal social support networks to mitigate health risks associated with job loss among older populations.